The box - Copyright Collection (Library of Congress) ([Place of publication not identified] : [Publisher not identified], 2009)
Screen siren star in the supernatural horror picture The Box (2008), directed by Donnie Darko cult fave Richard Kelly. The film's premise involves a strange and ominous box granted to a young couple by a mysterious stranger (Frank Langella). They are informed that pressing various buttons on the box will grant them riches while killing a person unknown to them in the process. Executive produced by Ted Hamm, the film was adapted by Kelly from Richard Matheson's 1970 short story Button, Button.
Summary taken from videocassette label.
Sources used: copyright data sheet; copyright data base; videocassette label.
Director Richard Kelly
Cameron Diaz, James Marsden, Frank Langella
Keywords: Dark Get-Rich-Scheme -- Fiction; Children's -- Animation -- Short; Educational -- Animation -- Short